CLIFF-GRADS Science Series 2020 - Special Session: Global agriculture production & emission trends - Porter, John R. (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Learn more about the CLIFF-GRADS Program and Alumni: https://ccafs.cgiar.org/CLIFF-GRADS